RAJASTHAN STATE WOMEN’S COMMISSION & WOMEN RIGHTS - Joshi, Vidhi; Mishra, Charu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Historical Background Our constitution was framed in 1948 to ensure equal right for men and women removing all kinds of discriminations based on caste, gender or religion. Government adopted several policies & programes to ensure women’s growth of empowement. Despite govt’s efforts women’s conditioned didn’t improve bedcause of continued violence against women. Women’s low literacy rate also was a cruicial factor behind their empowerment. In order to improve women condition govt. brought National Policy for women in 1996 to set up national commission for women & state commission for women.